Student workbook to accompany Medical assisting administrative and clinical procedures - Booth, Kathryn A. (Boston McGraw-Hill higher education, 2009)
The profession of medical assisting; Types of medical practice; Legal and ethical issues in medical practice, including HIPAA...
Includes index
Keywords: Medical assistants; Allied health personnel; Physicians’ assistants; Y tế